Association between the triglyceride glucose index and acute kidney injury following traumatic brain injury - Rujun Pan; Shaojie Li; Baofang Wu; Jiayin Wang; Shanglu Lin; Longjie Chen; De Wei; Hongzhi Gao (Scientific Reports)
Abstract Acute kidney injury (AKI) is associated with adverse hospitalization. Previous studies have reported that an elevated triglyceride glucose (TyG) index is significantly associated with the development of AKI in patients with cardiovascular disease, as well as in those undergoing surgery; however, the potential of the TyG index to predict AKI following neurotrauma remains unclear. Patients diagnosed with traumatic brain injury (TBI) in Chinese tertiary hospitals between January 2014 and December 2023 were included in this retrospective study. The outcome was the incidence of AKI. TyG was identified as an independent risk factor for AKI using logistic regression and propensity score matching (PSM). Finally, the association between TyG index and AKI was further assessed using multivariate logistic regression, restricted cubic spline (RCS) regression, and subgroup analysis. The present study enrolled 1,505 patients with TBI, of whom 66.45% were male, with an average age of 55.47 ± 17.32 years. The incidence of AKI was 9.4%. Multiple logistic regression analyses identified a relationship between the TyG levels and AKI risk. This relationship was retained after PSM. A significant positive correlation between TyG level and AKI was observed in all three models constructed using multivariate logistic regression. RCS regression analyses further indicated a linear increase in AKI risk with an increasing TyG index. In subgroup analyses, this correlation remained stable for the majority of the population but could be influenced by sex. TyG levels were positively correlated with the risk of AKI development in patients following TBI. As a predictive biomarker, the TyG index enables effective risk stratification and customization of management protocols to mitigate AKI in these patients, thus enhancing clinical outcomes.